FORMATION OF A SUBSTANTIVE CORE OF THE POLYSEMOUS VERB OF RELATIONS - Svetlana Kisselyova; Nelly Trofimova (Acta Mongolica, 2013)
This investigation is implemented within the cognitive approach and is dedicated to the formation of a substantive core of the polysemantic verb, particularly of the verb of relations in the modern English. The cognitive approach is suspected image mainstay as well as third meaning mainstay; it means the meaning of the speech act, which is realized by the speaker in the proper communicative situation or inside of the fitting context on the basis of the nominative and primitive terms, included in the words. The substantive core of the polysemantic word is appealed to integrate all its lexical semantic variants (LSV) and not to allow falling into homonyms.